Macroeconomics Indicator, Institutional Quality, and Public Private Partnership: A Case of Indonesia - Iklima Devi Grafitanti; Roby Syaiful Ubed (Journal of Theoretical and Applied Management (Jurnal Manajemen Teori dan Terapan), 2022)
Objective: This study aims to provide empirical evidence about the effect of macroeconomic conditions (inflation and GDP growth) and governance (control of corruption, stability politics, and voice and accountability) on private participation in PPP infrastructure projects in Indonesia as proxied by a total investment of PPP project. Design/Methods/Approach: This study uses secondary data with annual data for the period 2003 to 2019. The data sources are obtained from the World Bank Database (WGI, WDI, and PPI). Findings: The results show that inflation, GDP growth, and stability politic have no significant effect on the total investment of the PPP in Indonesia. Meanwhile, control of corruption has a significant positive effect on the total investment of PPP, and voice and accountability have a significant negative effect on the total investment of PPP projects in Indonesia. Originality: This study differs from previous research since variables such as inflation, GDP growth, political stability, corruption control, voice, and accountability have never been used in the Indonesian context. Practical/Policy implication (optional): These findings are likely to imply government to improve corruption control so that private participation in PPP projects increases and increasingly involves citizens' participation in PPP projects.